Management Physiotherapy Post Injection of the Platelet Rich Plasma (PRP) in the Case of Anterior Cruciate Ligament Tear: A Case Report - Sari, Wahyu Anita; Komalasari, Dwi Rosella; Maulana, Hakny (Universitas Muhammadiyah Surakarta, 2022)
Background: Anterior Cruciate Ligament (ACL) tear is a partial or complete tear of the ACL ligament. A torn ACL doesn't heal on its own. ALC tear can be treated with surgical and nonsurgical procedures, namely Platelet Rich Plasma (PRP) injectionandexercise.Objective: To report on the results of therapy in the treatment of ACL tears with PRP injection and exerciseMethods: Respondents aged 30 years experienced an ACL tear. After the PRP injection therapy, the patient was treated with Transcutaneous Electrical Nerve Stimulation (TENS) and an exercise program: quadriceps setting, hamstring setting, Straight Leg Raise (SLR), gluteus setting, bridging, walking squat, step up and step down, and balance training for approximately 1 hour each training session for 3 weeks with meetings 2 times a weekResults: Prior to the intervention, the patient complained of pain in his left knee and limited functional activities such as standing for more than 20 minutes, going up and down stairs and praying. Results after 3 weeks of physiotherapy intervention, there was a decrease in pain (silent pain: from 7 to 0, motion pain: from 10 to 5, tenderness: from 8 to 3) and an increase in functional activity.Conclusion: Observation of post-PRP injection on the ACL tear with Transcutaneous Electrical Nerve Stimulation (TENS) modality and an exercise program designed systematically and given from the start provide benefits in increasing functional activity.